2019
DOI: 10.2174/1570159x16666180419124508
|View full text |Cite
|
Sign up to set email alerts
|

Viral Induced Oxidative and Inflammatory Response in Alzheimer’s Disease Pathogenesis with Identification of Potential Drug Candidates: A Systematic Review using Systems Biology Approach

Abstract: Alzheimer's disease (AD) is genetically complex with multifactorial etiology. Here, we aim to identify the potential viral pathogens leading to aberrant inflammatory and oxidative stress response in AD along with potential drug candidates using systems biology approach. We retrieved protein interactions of amyloid precursor protein (APP) and tau protein (MAPT) from NCBI and genes for oxidative stress from NetAge, for inflammation from NetAge and InnateDB databases. Genes implicated in aging were retrieved from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 158 publications
0
20
0
1
Order By: Relevance
“…21 Furthermore, another study also found that HPV may also play a role in inducing oxidative and inflammatory response in Alzheimer's disease pathogenesis. 22 On the other hand, some researchers have found that the E6 and E7 genes of HPV 16 could protect astrocytes, 23,24 which have essential roles implicated in the pathogenesis of neurodegenerative disease, 25 from injury. Therefore, further studies are needed to investigate the association between HPV and the risk of dementia by using a nationwide database in Taiwan.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 Furthermore, another study also found that HPV may also play a role in inducing oxidative and inflammatory response in Alzheimer's disease pathogenesis. 22 On the other hand, some researchers have found that the E6 and E7 genes of HPV 16 could protect astrocytes, 23,24 which have essential roles implicated in the pathogenesis of neurodegenerative disease, 25 from injury. Therefore, further studies are needed to investigate the association between HPV and the risk of dementia by using a nationwide database in Taiwan.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that HPV may be detected in neurological diseases, for example, in the brains of patients with pediatric epilepsy and Rasmussen’s encephalitis . Furthermore, another study also found that HPV may also play a role in inducing oxidative and inflammatory response in Alzheimer’s disease pathogenesis . On the other hand, some researchers have found that the E6 and E7 genes of HPV 16 could protect astrocytes, which have essential roles implicated in the pathogenesis of neurodegenerative disease, from injury.…”
Section: Introductionmentioning
confidence: 99%
“…Out of the three APOEs, APOE □4 was the least potent and effective at preventing HIV-1 internalization 65 . To complete this model, it is highly likely that viral infection is accompanied by the activation of microglia cells causing inflammation including activation of TREM2 59,66,67 , corresponding to another AD susceptibility gene. Further research is necessary to underline this hypothetical model, which supports the benefit of an antiviral therapy for the treatment of AD as recently initiated 68 .…”
Section: Discussionmentioning
confidence: 99%
“…Degenerative diseases of the brain that have been linked to altered RAS include Parkinson disease, Alzheimer disease, Huntington disease, multiple sclerosis, amyotrophic lateral sclerosis, traumatic brain injury, other than stroke as mentioned above (86,98,99). Moreover, the dysregulation of the antiviral response is another factor that has been associated with neurodegenerative disease (100,101). It has been shown that products of certain genes may have potent antiviral activities, and may have deleterious effects when their expression is not appropriately regulated.…”
Section: Long Term Complication Of Covid 19 Invasion In the Brainmentioning
confidence: 99%